Kajian Hukum terhadap Perempuan Pengedar Narkotika dalam perspektif Kriminologi (Studi di Lembaga Pemasyarakatan Perempuan Klas IIA Tanjung Gusta) - iin Hotprinauli Purba (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
Narcotics is a drug that is indispensable in the field of medicine and science but can also lead to dependence on narcotics if used without careful limitation and supervision. In the implementation of health services, narcotics play an important role because these narcotics are used for the benefit of science, research, development of education and teaching so that they need supervision in the circulation of narcotics in Indonesia. Narcotics dealers are people who carry out the distribution and delivery of narcotics. Broadly, the definition of "dealer" can also be done and oriented to the dimensions of the seller, the buyer to circulate, transport, store, control, provide, carry out the act of exporting and importing Narcotics.Narcotics addicts in Indonesia continue to increase, this is inseparable from the role of narcotics dealers, in fact it can be said that the root of the high number of narcotics addicts in Indonesia comes from the increasing circulation of illegal narcotics in the community. The phenomenon of narcotics crimes committed by women has now been seen as a critical issue considering the number that continues to grow from time to time. The involvement of women in narcotics abuse has been very dangerous so that researchers conducted a thesis research entitled "Legal Review of Women Narcotics Dealers in the Criminology Perspective (Study at Tanjung Gusta Class IIA Women's Penitentiary)"Researchers suggest an understanding of the responsibility of fostering prisoners with all parties, particularly components in the criminal justice system such as the police, prosecutors and judiciary by actively involving the community, and the need for participation of the government and the private sector in efforts to deal with obstacles faced by prisons.Keywords:  Distributors, Narcotics, Women, Correctional Services.